Localized scleroderma en coup de sabre in the Neurology Clinic - Pinho, João (2016)
Background: Localized scleroderma en coup de sabre (LScs) is a form of localized scleroderma thought to be an autoimmune disorder. Central nervous system involvement is not rare and neurological manifestations include seizures, focal neurological deficits, headache and neuropsychiatric changes. Methods: Patients attending the Neurology Clinic with the final diagnosis of LScs with neurological manifestations were identified and clinical and imagiological records reviewed. Results: Five patients (0.024%) had LScs with neurological involvement, presenting with transient focal neurologic deficits, seizures, headache or migraine with aura. Neuroimaging studies confirmed localized skin depression and showed bone thinning, white matter lesions, brain calcifications, sulcal effacement and meningeal enhancement. Three patients experienced clinical improvement after immunosuppressive therapy, and in two of these patients neuroimaging findings also improved. Conclusions: Recognizing typical dermatologic changes is keystone for the diagnosis of LScs with neurological involvement. It is a diagnosis of exclusion and extensive etiological diagnostic evaluation should be performed. Treatment options, including conservative follow-up or immunosuppressive therapy, should be carefully considered.